Cavitated Conglomerate Mass in Silicosis Indicating Associated Tuberculosis - Pedro Martins; Edson Marchiori; Gláucia Zanetti; Antonio Muccillo; Nina Ventura; Viviane Brandão; Mariana Leite Pereira; Carolina Pesce Lamas Constantino; Guilherme Abdalla; Romulo Varella de Oliveira; Rodrigo Canellas (Case Reports in Medicine)
Silicosis is the most common occupational lung disease worldwide. It leads to respiratory impairment and may have associated infections that decrease pulmonary function. We describe the case of a 55-year-old man with chronic silicosis who presented with hemoptysis and a cavitated conglomerate mass. The final diagnosis was silicotuberculosis.